Metabolites Associated With Regression to Normoglycemia After a Lifestyle Intervention in Individuals With Prediabetes. (7th June 2021) - Sevilla-Gonzalez, Magdalena; Deik, Amy; Manning, Alisa; Clish, Clary B
Abstract: Objectives: Prediabetes is a highly prevalent intermediate stage between normal glucose tolerance and type 2 diabetes (T2D). Lifestyle interventions (LSI) are the main focus for T2D prevention, but little is known about the aspects of LSI that can lead to the regression to a normal glucose regulation (RNGT). Metabolomics can be a helpful tool to identify the footprints of RNGR. Our aim was to identify the metabolites and lifestyle aspects that contribute to RNGR in prediabetes. Methods: We conducted a one arm intervention study with 24 weeks of follow-up. Eligible study participants were identified by having at least one prediabetes criteria according to the American Diabetes Association, and BMI between 25 and 45 kg/m 2 . The LSI was a hypocaloric diet and >150 min of physical activity at a medium intensity per week. The primary outcome, RNGR was defined as HbA1c < 5.5% in the final visit. Baseline and post-intervention plasma metabolomic profiles were measured using liquid chromatography-tandem mass spectrometry (LC-MS). To select metabolites associated with RNGT we conducted the least absolute shrinkage and selection operator-penalized regression (LASSO). Results: The final sample was composed of 82 study participants. We observed that individuals who increased their protein consumption were more likely to have RNGR compared to controls (HR 0.97 95%CI 0.94–0.99), adjusted by age, sex, HbA1c at baseline, and weight loss. At baseline, participants with RNGT had lower plasma sphinganine (OR per standard unit 0.51; 95%CI 0.27–0.96), and higher levels of myristoleic acid (OR 2.31; 95%CI 1.16 – 4.59). After the intervention, compared with controls, RNGT individuals had higher plasma levels of amino acids and other metabolites: threonine (OR 3.19; 95%CI 1.53–6.66), alanine (OR 3.09; 95%CI 1.49–6.43), proline (OR 1.95; 95%CI 1.02–3.73), and prolylglycine (OR 2.19; 95%CI 1.53–6.66), 4-guanidinobutanoic acid (OR 1.98; 95%CI 1.07–3.64), Ne, Ne-dimethyllysine (OR 2.08; 95%CI 1.14–3.80), urate (OR 2.22; 95%CI 1.13–4.36), biliverdin (OR 1.57; 95%CI 1.13–4.36), and Asymmetric dimethylarginine (OR 2.04; 95%CI 1.10–3.77). Conclusions: Some metabolites could be associated with RNGT independently of other treatment aspects such as weight loss. Increased protein consumption could have a positive impact on the treatment of individuals with prediabetes. Funding Sources: MGH.